The Influence of Solar Sintering on Copper Heat Exchanger Parts with Controlled 3D-Printed Morphology - Pop, Mihai Alin; Croitoru, Cătălin; Bedo, Tibor; Geamăn, Virgil; Radomir, Irinel; Crișan, Aurel; Guillot, Emmanuel; Milosan, Ioan; Zaharia, Sebastian Marian; Chicoș, Lucia Antoaneta (MDPI AG, 2022)
: From a scientific point of view, heat transfer is different in solar furnaces compared with classical ones and the influence of direct concentrated solar radiation on sintered parts needs to be studied in detail to determine the feasibility of solar furnaces in manufacturing small workpieces. This study was performed on cylindrical samples with controlled morphology obtained by a powder metallurgy 3D printing technique. All samples were heated with a heating rate of 120 ± 10 ◦C/minute, with 0, 1, 2, 3, 4 and 5 min holding times at 900 ◦C and 930 ◦C. The morphology of the samples was analyzed microscopically, the microhardness was determined before and after sintering, and the results were correlated with the sintering parameters (temperature, heating rate and holding time). The best results were obtained at 930 ◦C with 5 min holding time from the microhardness value and microstructure point of view.
Keywords: powder metallurgy; 3D printing; concentrated solar energy